Immunosuppressive tumor microenvironment in uterine serous carcinoma via CCL7 signal with myeloid-derived suppressor cells. (30th March 2022) - Mise, Yuka; Hamanishi, Junzo; Daikoku, Takiko; Takamatsu, Shiro; Miyamoto, Taito; Taki, Mana; Yamanoi, Koji; Yamaguchi, Ken; Ukita, Masayo; Horikawa, Naoki; Abiko, Kaoru; Murakami, Ryusuke; et al.
Abstract: Serous carcinoma of the uterus (USC) is a pathological subtype of high-grade endometrial cancers, with no effective treatment for advanced cases. Since such refractory tumors frequently harbor antitumor immune tolerance, many immunotherapies have been investigated for various malignant tumors using immuno-competent animal models mimicking their local immunities. In this study, we established an orthotopic mouse model of high-grade endometrial cancer and evaluated the local tumor immunity to explore the efficacy of immunotherapies against USC. A multivariate analysis of 62 human USC cases revealed that the tumor-infiltrating cell status, few CD8+ cells and abundant myeloid-derived suppressor cells (MDSCs), was an independent prognostic factor ( P < 0.005). A murine endometrial cancer cell (mECC) was obtained from C57BL/6 mice via endometrium-specific deletion of Pten and Tp53, and another high-grade cell (HPmECC) was established by further overexpressing Myc in mECCs. HPmECCs exhibited higher capacities of migration and anchorage-independent proliferation than mECCs ( P < 0.01, P < 0.0001), and when both types of cells were inoculated into the uterus of C57BL/6 mice, the prognosis of mice bearing HPmECC-derived tumors was significantly poorer ( P < 0.001). Histopathological analysis of HPmECC orthotopic tumors showed serous carcinoma-like features with prominent tumor infiltration of MDSCs ( P < 0.05), and anti-Gr-1 antibody treatment significantly prolonged the prognosis of HPmECC-derived tumor-bearing mice ( P < 0.05). High CCL7 expression was observed in human USC and HPmECC, and MDSCs migration was promoted in a CCL7 concentration-dependent manner. These results indicate that antitumor immunity is suppressed in USC due to increased number of tumor-infiltrating MDSCs via CCL signal. Abstract : Uterine serous carcinoma (USC) is a high-grade subtype of endometrial cancers with no effective treatment. We established an orthotopic mouse model of high-grade endometrial cancer and evaluated the tumor microenvironment to explore the efficacy of immunotherapies against USC. Graphical Abstract: